Simultaneous analysis of Cr(III), Cr(VI), and chromium picolinate in foods using capillary electrophoresis‐inductively coupled plasma mass spectrometry. Issue 9 (20th April 2015) - Chen, YiQuan; Chen, JinFa; Xi, Zhiming; Yang, Guidi; Wu, Zujian; Li, JianRong; Fu, FengFu
Abstract : We herein reported a method for the simultaneous detection of trace Cr(VI), Cr(III), and chromium(III) picolinate (CrPic) in foods using CE‐ICP‐MS together with ultrasonic‐assisted extraction. The Cr(III) (Cr 3+ ) was chelated with trans‐1, 2‐diaminocyclohexane‐ N, N, N ´, N ´‐tetraacetic acid (DCTA) to form a single charged Cr‐DCTA − complex. Then, Cr(VI) (CrO4 2− ), Cr‐DCTA −, and CrPic were separated by CE within 8 min under a separation voltage of –13 KV followed by their monitoring with ICP mass spectrometer (ICP‐MS). The proposed method is simple, effective, and sensitive. It has an instrument detection limit of 0.10, 0.18, and 0.20 ngCr/mL for Cr(VI), Cr(III), and CrPic, respectively. With the help of the methods, we have successfully determined Cr(VI), Cr(III), and CrPic in nutritional supplement (CrPic yeast tablet) with an RSD ( n = 5) <6% and a recovery of 93–103%. The experimental results showed that CrPic was the main speciation of chromium in the nutritional supplement, with a concentration of 1514.6 μg Cr/g.